Algoritmos de otimização para priorização da modernização da proteção em redes elétricas - Ramon Lacerda Marques (2016)
This thesis proposes a set of algorithms and methods to evaluate the impact of replacing directional overcurrent relays in distribution and transmission networks. The performance of the protection under the current system state (reference case) is assumed as the benchmark for testing alternative situations, considering the replacement of some devices by more efficient ones. A fast coordination tool and three optimization algorithms were proposed to generate suitable solutions to the problem. These algorithms were designed to minimize the total operation time of the relays, in order to ensure better response in the presence of faults. The robustness of the network before and after the adoption of the proposed solutions is also evaluated. The results for three literature instances demonstrate that the proposed methods can assist the protection engineer on making decisions with regard to the replacement of power system relays.